Crack Propagation Mechanism of Hydraulic Fracturing in Thick-Bedded Sandstone Coal Mine Roof. Issue 4 (October 2021) - Zhao, Shankun; Yao, Maohong; Li, Yingjie; Chai, Haitao; Zuo, Jianping
Abstract: The thick-bedded sandstone roof of the Bayangaole coal mine is at risk of rock burst accidents. Hydraulic fracturing technology has been used to prevent these accidents by controlling coal seam roof collapse. To research the crack propagation mechanism of hydraulic fracturing in thick-bedded sandstone roof, hydraulic fracturing experiments are conducted on thick roof sandstone with a hole drilled in the center, and RFPA2D-Flow software is adopted to conduct numerical simulations of the formation mechanism and spatial distribution of hydraulic fracture cracks in bedded sandstone. The physical experiments reveal that cracks are generated from the weak parts and stress-concentration area of the hole wall due to hydraulic pressure; main cracks either form along the bedding or spread toward the bedding. Numerical simulations show that the crack propagation mechanism for specimens without preset slotting is consistent with the experimental results. For the preset-slot specimens, micro-cracks generate in the region where tensile stress is applied, which gradually increase and penetrate the preset slotting tip; the specimen continues to crack until failure occurs. When the main crack encounters the bedding, it turns and propagates along the bedding when the bedding angle is small, which results in tensile failure. However, when the angle is large, the crack passes directly through the bedding, forms a new hydraulic crack, and continues to propagate forward, which results in the tensile failure of the cutting bedding.